2021
DOI: 10.1007/s11538-021-00919-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Relationship Between Antibody-Dependent Enhancement and Disease Severity in Secondary Dengue Infection

Abstract: Sequential infections with different dengue serotypes (DENV-1, 4) significantly increase the risk of a severe disease outcome (fever, shock and hemorrhagic disorders). Two hypotheses have been proposed to explain the severity of dengue disease: (1) antibody-dependent enhancement (ADE); (2) original T cell antigenic sin. In this work, we explored the first hypothesis through mathematical modeling. The proposed model reproduces the dynamic of susceptible and infected target cells, and dengue virus in scenarios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Tere have been various immune responses studied in secondary DENV infections, among them: secondary DENV infection model with humoral immunity by [20,24,30], both humoral and CTL immunity [22,27], the mobility of cells and viruses has been studied by [25], Alshaikh et al [26] developed a model of secondary DENV infection that takes into account that the DENV can infect multiple classes cell types, Alves Rubio et al [32] studied and analyzed a mathematical model to explain antibody-mediated enhancement in heterologous of secondary infections and assess the efect of limiting cloning for plasma cells. Te following model is a secondary DENV infection model with humoral immunity, which was introduced by [30]:…”
Section: Primary and Secondary Denv Dynamics Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tere have been various immune responses studied in secondary DENV infections, among them: secondary DENV infection model with humoral immunity by [20,24,30], both humoral and CTL immunity [22,27], the mobility of cells and viruses has been studied by [25], Alshaikh et al [26] developed a model of secondary DENV infection that takes into account that the DENV can infect multiple classes cell types, Alves Rubio et al [32] studied and analyzed a mathematical model to explain antibody-mediated enhancement in heterologous of secondary infections and assess the efect of limiting cloning for plasma cells. Te following model is a secondary DENV infection model with humoral immunity, which was introduced by [30]:…”
Section: Primary and Secondary Denv Dynamics Modelsmentioning
confidence: 99%
“…Among the studies that introduced DENV infection, taking into account difusion, was Elaiw and Alof study [25], they modeled a DENV infection with difusion, by taking into consideration the spatial mobility of cells and DENV particles. Furthermore, [25] considered the DENV can infect one target of cells, but there are several works that have indicated that the dengue virus can infect multiple types of cells (e.g., [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]).…”
Section: Primary and Secondary Denv Dynamics Modelsmentioning
confidence: 99%
“…Mathematical models of secondary DENV infection were recently introduced in several works (see e.g., [17] , [18] , [19] , [20] , [21] , [22] ). The effect of immune response was considered in the secondary DENV infection models such as: antibody immune response [17] , [18] , [19] , [21] , CTL immune response [7] , [13] , both antibody and CTL immune responses [20] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…(i) The regeneration and death of the uninfected monocytes are not included. However, in the literature, several DENV infection models considered the regeneration and death of the uninfected monocytes (see e.g., [17] , [19] , [20] , [21] ). The population dynamics equation for the uninfected monocytes was given as: where ρ and σU represent the regeneration and death rates of the uninfected monocytes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ceron et al [ 18 ] established a dengue virus model with ADE, and evaluated the effect of the ADE phenomenon on heterologous dengue infection. Based on infection-neutralizing and infection-enhancing antibody competition scenarios, Camargo et al [ 19 ] modeled the dynamics of secondary infection induced by two different serotypes of dengue virus, and calculated the time when the maximum enhancing activity for the infection occurs. By extending the basic model of viral dynamics, Danchin et al [ 20 ] established neutralizing and weakly neutralizing scenarios, and they found that both weakly neutralizing antibodies and ADE could lead to eventual viral clearance or disease progression.…”
Section: Introductionmentioning
confidence: 99%